طرق علاج الفقر في الإسلام-الوقف أنموذجا - موساوي, جباري (University of eloued جامعة الوادي, 2016)
الحمد لله رب العالمین والصلاة والسلام على المبعوث رحمة للعالمین وعلى آله وصحبه أجمعین أما بعد: تعرضت في هذه الرسالة لمعضلة الفقر بالتحلیل والد ا رسة كظاهرة في المجتمع الإنساني، وإب ا رز أحد طرق علاجها في الإسلام والمتمثل في الوقف من أجل الرقي إلى وضع أنساني أفضل والمتمثل في في علاج أحد المشكلات التي یعانیها العالم الإسلامي، وهي في نفس الوقت دعوة لإقامة نظام وقفي یقلل من هذه الظاهرة. وتعرض هذه الد ا رسة إحدى الوسائل التي یعتمد علیها الإسلام لضمان حد الكفاف والتخفیف من مدة الفقر والمتمثلة في الوقف الإسلامي، ومدى دوره إن استغل على الوجه المشروع بالإضافة إلى الآلیات الأخرى المكملة التي هي جزء من الخصوصیة الحضاریة للإسلام. Praise be to Allah, prayer and peace envoy mercy to the worlds and his family and companions either: It has been in this letter to the dilemma of poverty analysis and study a phenomenon in human society, and to highlight one of methods of treatment in Islam and of the moratorium in order to progress to the humanitarian situation the best of in the treatment of one of the problems that the Muslim world suffers, which sat the same time call for the establishment of an endowment system reduces This phenomenon. This study presents one of the meansuponwhich Islam to ensure the subsistence level and duration of alleviation of poverty and of the Islamic Waqf, and how to take advantage of his role on the face of the project as well as other complementary mechanisms that are part
معاملات المالية
Keywords: الفقر/الإسلام/الوقف; Poverty/Islam/Waqf